CREATIVE AND PEDAGOGICAL CONCEPT "APPLE IN A LEAF" BY VITALY LENCHIN AND WAYS OF ITS FORMATION - Найденко, В. О. (Art and Design, 2023)
The purpose of the article is to analyze one’s own version of the creative method and form of artistic expression in the creative and pedagogical activity of the Kharkiv graphic artist V. Lenchin in the context of avant-garde searches of Ukrainian art by the second half of the 20th century – beginning 21st century, reflected in the author’s concept "Apple in a leaf" and revealing the ways of its formation. Methodology. General scientific methods are used, including analysis and synthesis, induction and deduction, analogy, as well as biographical, historical and cultural, iconographic and iconological, artistic and stylistic analysis and comparative methods. The results. The article explores the creative-pedagogical concept of form-making, titled "Apple in a leaf," by Vitaly Lenchin, a representative of the Kharkiv School of Graphics in the second half of the 20th century – beginning of the 21st century. The factors that influenced the formation of his artistic worldview and the development of his own version of painting in the context of contemporary avant-garde searches in Ukrainian art are outlined. It was revealed that form and experiments with it occupied a special place in the artistic philosophy of the master. It was determined that V. Lenchin considered the thinking process and the need to have a "conscious eye" to reflect reality and create a form in the paper as fundamental in drawing. The article analyzes individual works of the artist that have not been published or analyzed before. It also highlights the importance of figurative and plastic and methodical innovations of the master in the context of the revival of the avant-garde tradition in Ukrainian artistic culture during the studied period. Scientific novelty. For the first time in Ukrainian art history, a study of the author’s concept of visual art of the Kharkiv graphic artist-experimenter V. Lenchin, titled "Apple in a leaf" was conducted as one of the variants of avant-garde searches in Ukrainian art by the second half of the 20th century – beginning 21st century. Practical significance. The results of this investigation can be used in lecture materials and for further research on Ukrainian art from the second half of the 20th century – beginning of the 21st century. Additionally, they can contribute to the creation of new methods and educational programs currently relevant.